Analisis Pendidikan Karakter Siswa Kelas III Berdasarkan Kompetensi Sosial Guru Mata Pelajaran IPAS di SDN Talun 05 - Oktaviarini, Nourma; Astuti, Leny Suryaning (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Character education is a variety of efforts made by schools, parents, and communities to help students become human beings who have caring, opinionated, and responsible traits. Success in the learning process cannot be separated from the importance of the role of the teacher. Teachers are required to master various competencies needed in carrying out the duties of being a good educator, one of which is social competence. The purpose of this study was to analyse and describe the character education of third grade students based on the social competence of IPAS subject teachers at SDN Talun 05 Talun District, Blitar Regency. The type of research used in this study is descriptive qualitative research. The data collection method uses questionnaires, interviews, and documentation. The results showed that the value of student character education was very good with the results of the questionnaire showing a percentage of 87.92%. the social competence of the third grade teacher at SDN Talun 05 was very good with the results of the questionnaire showing a percentage of 89.17%. It can be concluded that the social competence of teachers is very important in shaping the value of student character education